Measuring system for the control of the person acupuncture points activity at stationary and non-stationary conditions - Azarov, O. D.; Snihur, A. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Measuring system for the control of the person acupuncture points activity at stationary and non-stationary conditions on base of ADC with weight redundancy is developed. It is shown, that the system enables the opportunity to restore periodically metrological characteristics of its «nucleus» — ADC in non-stationary conditions as performance of the so-called procedure of selfcalibration which allows to reduce or eliminate the influence of external factors on final results of measurements.